Application of molecular tools to update aquatic ecotoxicology monitoring - Manfredi, Valeria (2024)
The field of aquatic ecotoxicology studies the structural and functional disturbances induced in the short, medium, and long-term by contamination factors on ecological aquatic systems. Traditionally, organisms selected for the ecotoxicity studies are identified morphologically. Zooplankton communities are frequently employed as indicators of ecological shifts in water quality, serving to monitor such changes (Hemraj et al., 2017; Parmar et al., 2016). Because of their quick and prolific reproduction, zooplankton respond promptly to environmental alterations (Parmar et al., 2016), although they are still poorly studied.